Necesidad de precautelar el interés del alimentante en los procesos de alimentos mediante la incorporación de la rendición de cuentas del destino de los valores de las pensiones alimenticias en el código de la niñez y adolescencia - Zambrano Bravo, Patricio Eduardo (2014)
Children and adolescents throughout history has tried to give a special and preferential protection, so that the various international treaties and conventions has given emphasis to this situation; the same way the various Constitutions of the Republic have recognized this, the current Constitution is no exception determines that the State, society and family a priority promote the integral development of children and adolescents, and ensure the full exercise of their rights; will be addressed at the beginning of their interests and their rights shall take precedence over those of others. The integral development must understand it as a process of growth, maturation and deployment of their intellect and their abilities, potential and aspirations, in the family, school, social and community environment of affection and security. It comprises the environment or the landscape of comprehensive protection of this group of people requires some key elements such as food, clothing, housing, medical care, education, recreation and others; is why the Code of Childhood and adolescence is wise to determine that the right food is inherent in the parent-child relationship is related to the right to life, survival and a decent life. Implies the guarantee of providing the resources necessary to meet the basic needs of food, including: 1 nutritious, balanced and sufficient supply; 2 Integral health: prevention, care and provision of medicines; 3 Education; 4 Care; 5. appropriately dressed; 6. safe, hygienic and provided with basic services Housing; 7 Transportation; 8 Culture, recreation and sports; and, Rehabilitation and assistive 9 if the person entitled hath any temporary or permanent disability. And with understanding this concept must consider that in the process of food three people, the obligor, the food and its representative involved. While it is determined that the correct target is given alimony there would be no problem, but reality has shown us very different cases where the representative uses his judgment and values benefit received by way of maintenance for less, that certainly upsets the true spirit of the right to food. The Act establishes the principle of legal responsibility therefore must be considered and the destination and correct use of the value of maintenance, these are justified by the representatives; which would correspond with that determined in Civil Code in cases of guardians and conservators where it is determined that the guardian is required to pay documented financial statements of their care, so that you can demonstrate the need to safeguard everyone's interest obligor in food processes by incorporating accountability for the fate of the values of maintenance the code of childhood and adolescence.